A Buddhist Approach to Happiness by Loving-Kindness (Mettā) for Medical Personel in New-Normal Age - Sudprasert, Saowapa; Mahatthanadull, Sanu (Journal of International Buddhist Studies, 2021)
This article aims to explore a Buddhist approach to happiness by loving-kindness (mettā) for medical personnel in new-normal age. There are a number of obstacles associated with medical personnel, especially with respect to obtaining their approval for routine use from various substantial personal protective equipment shortages, insufficient of the medical personnel, complication of care, and fear of changes. The Buddhist approach to make happiness in order to solve the obstacles of medical personnel that loving-kindness (mettā) is the fundamental principle to bring happiness. Due to mettā goes hand in hand with helpfulness and willingness to forego self-interest in order to promote the welfare and happiness of mankind. Happiness can defined as life-satisfaction, subjective well-being, and good life and denotes a state of mind. Mind developed by loving-kindness (mettā). Mettā is a multi-significant meaning as goodwill, loving-kindness, universal love, a feeling of friendliness and heartfelt, the sincere and genuine wish for the welfare and happiness of all living beings without exception and concern for all living beings, human or non-human, in all situations all over the world. Loving-kindness mettā should be practiced first towards oneself, then other. Therefore, loving-kindness plays most essential role for creating inward happiness for medical personnel in new-normal age.